Performance and Management of Cost in the Construction Industry - Fazal Ali Shaikh; Nasurullah Odhano; Suaathi Kaliannan (Civil Engineering Journal, 2020)
In the arena of cost baselines and project budgets, the construction industry is always famed and controversial. Owing to the paucity of funds or maladministration at various levels, there is 90 percent of project delay is fully stranded. While being a major contributor to a country's Gross Domestic Product, its sufficient potentiality has never been tapped. Maybe this dismaying climate is created by the cold-hearted, reckless and unscrupulous attitudes of construction industry stakeholders. The main objectives of this research is to determine the genesis of exceeded budget/cost in construction projects that affect cost management and to suggest appropriate measures to harness the construction industry's full potential. The key drivers that have positive or negative repercussions on the cost aspect of the projects are the administration, pundits and consumers or holders. For assessing the most common causative factors of exceeded cost in construction projects, the authors organized interactive discussions with construction industry pundits, designers, architects, schematic experts, and manufacturers. Moreover, the incumbent concerns in the construction industry were analyzed and examined to examine important factors. To underscore the key motives that drive the projects, directly and indirectly, a questionnaire was dispensed between the participants on the analysis in the cost of undergoing projects. Results of the study are the key interpretations which were drawn from this research paper are fraud, weak political engrossment, poor site management, hampering of site deployment, consultants inflexible approach, gold plating, faulty safety and healthcare management system. To remove these hurdles, I have recommended appropriate guidelines for preventing, reducing or mitigating the effects of these factors.